Karakteristik Pertumbuhan Kandidat Mutan Lamtoro (Leucaena leucocephala cv. tarramba) Generasi M1 Toleran Cekaman Masam pada Skala Lapang : Growth Characteristics of M1 Generation Candidate Mutants of Lamtoro (Leucaena leucocephala cv. tarramba) Tolerant to Acid Stress on Field Scale - azwa lubis, fadhilatul; Prihantoro, Iwan; Karti, Panca Dewi Manuhara (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2024)
The selected of lamtoro var. tarramba mutant candidates tolerant to pH 3.8 are expected to grow well in a normal field-scale environment. The purpose of this study was to evaluate the growth characteristics of mutant candidates of lamtoro var. tarramba M1 generation tolerant to acid on field. This study used Randomized Block Design (RBD) of 11 mutant candidates of lamtoro var. tarramba (T1-T11) consisting of five replications. The variables measured included plant morphology (plant height, stem diameter, number of branches, and number of stalks) rhizosphere pH, and rhizosphere color. The results showed that the growth characteristics of mutant candidates of lamtoro var. tarramba M1 generation tolerant to acid pH 3.8 on field scale were equally good for parameters of plant height, stem diameter, number of branches, and number of stalks. The conclusion of the study was that the total of 11 acid-tolerant lamtoro var. tarramba mutant candidates of M1 generation were able to grow well on a field scale. All M1 generation mutant candidates produced the same good growth characteristics of plant height, stem diameter, number of branches, and number of stalks at the end of the study (8 WAP). Key words: acid tolerant, growth characteristics, lamtoro var. tarramba mutant, M1 generation